Analysis of Hybrid Work Model on Employee Performance Through Work Life Balance - Fatyandri, Adi Neka; Wijaya, Antonio Tantra; Muchsinati, Evi Silvana (SENTRALISASI, 2025)
This study aims to determine the effect of hybrid work systems on employee performance through work life balance in the insurance services industry in Batam City. With data collection that has been done through the distribution of questionnaires in Batam City involving 264 respondents, with the majority of men aged 18-25 years, with a high school / vocational high school education background, working as staff. The results of the hypothesis testing indicate that work life balance can be supported by the implementation of a hybrid work model. However, increasing this work life balance does not always contribute directly to improving employee performance. Further research is recommended to identify other factors or variables that can provide new insights in explaining the impact of hybrid work systems on employee performance.